I will not eat you - Lehrhaupt, Adam; Magoon, Scott (New York : Simon & Schuster Books for Young Readers, 2016)
A dragon resists the urge to eat the animals that approach his cave.
Keywords: Dragons -- Fiction; Animals -- Fiction; Friendship -- Fiction